Retention of total phenolic content and antioxidant activity in the concentration of broccoli extract by progressive freeze concentration - Azhar, A.N.H. (De Gruyter Open Ltd, 2020)
A conventional evaporation is known to involve high temperature process which could destroy the heatsensitive compound in a plant extract. In this study, a green and low-cost alternative concentration technique namely progressive freeze concentration (PFC) has been introduced to concentrate broccoli extract. A stirred cylindrical crystallizer was used to freeze the added solvent (water) in the extraction process. The changes in effective partition constant (K), antioxidant activity (AA) and total phenolic content (TPC) of the extract, were analysed at a different reading of coolant temperature, freezing time and stirring rate. From the findings, it was found that an amount of 0.003180 mg GAE/g of total phenolic content and 86.10 of antioxidant activity were retained through the PFC process at a coolant temperature of -6 Â°C, freezing time of 45 min and stirring rate of 100. Besides, the lowest K value achieved was 0.08 which outstandingly portrays an efficient PFC process. Â© 2020 De Gruyter. All rights reserved.